Lactococcus lactis Expressing Type I Interferon From Atlantic Salmon Enhances the Innate Antiviral Immune Response In Vivo and In Vitro - Muñoz, Carlos; González-Lorca, Josue; Parra, Mick; Soto, Sarita; Valdes, Natalia; Sandino, Ana María; Vargas, Rodrigo; González, Alex; Tello, Mario (Frontiers in Immunology, 2021)
In salmon farming, viruses are responsible for outbreaks that produce significant economic losses for which there is a lack of control tools other than vaccines. Type I interferon has been used successfully in treating some chronic viral infections in humans. However, its application in salmonids depends on the proper design of a vehicle that allows its massive administration, ideally orally. In mammals, administration of recombinant probiotics capable of expressing cytokines has shown local and systemic therapeutic effects. In this work, we evaluate the use of Lactococcus lactis as a type I Interferon expression system in Atlantic salmon, and we analyze its ability to stimulate the antiviral immune response against IPNV, in vivo and in vitro. The interferon expressed in L. lactis was located mainly in the bacterial cytoplasm; however, it was functional, being able to stimulate the Mx and PKR expression in CHSE-214, and to reduce the IPNV viral load in SHK-1 cells. In vivo, the oral administration of this L. lactis producer of Interferon I increases Mx and PKR expression, mainly in the spleen, and to a lesser extent, in the head kidney. The oral administration of this strain also reduces the IPNV viral load in Atlantic salmon specimens challenged with this pathogen. Our results show that oral administration of L. lactis producing Interferon I creates systemic effects in Atlantic salmon, allowing to stimulate the antiviral immune response. This probiotic could have effects against a wide variety of viruses that infect Atlantic salmon and also be effective in other salmonids due to the high identity among their type I interferons.